(untitled) (The Peerian Journal, 2024)
The research includes four chapters, (Chapter One) the methodological framework of the research, which contains the research problem centered on the following question: What is the concept of the body according to contemporary artistic visions and trends, and did the connotations of the body according to contemporary intellectual and artistic trends have an impact on the meaning of the body as a concept and symbol? Did social changes and transformations play a role in changing the concept of the body? The aim of the research was based on introducing the concept and representations of the body in contemporary plastic art and in potters specifically, and shedding light on the concept of the human body in accordance with intellectual and cultural currents and aesthetic transformations in the field of potters and contemporary plastic arts, and exploring the relationship between the symbols and connotations of the body in life and art, through analysis a selected samples of potters who dealt with the subject of the body in their artistic works, within the temporal limits (1990-2020), and the chapter concluded by defining the most important terms mentioned in the title of the research.